## Step 1 :

Equation at the end of action 1 : (2x2 - 5x) - 3 = 0

## Step 2 :

Trying to factor by separating the middle term2.1Factoring 2x2-5x-3 The first term is, 2x2 that is coefficient is 2.The middle term is, -5x the coefficient is -5.The critical term, "the constant", is -3Step-1 : main point the coefficient that the an initial term through the constant 2•-3=-6Step-2 : find two factors of -6 who sum amounts to the coefficient that the center term, i m sorry is -5.

 -6 + 1 = -5 That"s it

Step-3 : Rewrite the polynomial splitting the center term making use of the two determinants found in step2above, -6 and 12x2 - 6x+1x - 3Step-4 : add up the first 2 terms, pulling out choose factors:2x•(x-3) add up the last 2 terms, pulling out typical factors:1•(x-3) Step-5:Add up the 4 terms that step4:(2x+1)•(x-3)Which is the preferred factorization

Equation in ~ the finish of action 2 :

(x - 3) • (2x + 1) = 0

## Step 3 :

Theory - roots of a product :3.1 A product of numerous terms equals zero.When a product of 2 or more terms amounts to zero, climate at the very least one that the terms have to be zero.We shall currently solve every term = 0 separatelyIn other words, we room going to resolve as numerous equations as there space terms in the productAny equipment of ax = 0 solves product = 0 as well.

Solving a solitary Variable Equation:3.2Solve:x-3 = 0Add 3 come both political parties of the equation:x = 3

Solving a solitary Variable Equation:3.3Solve:2x+1 = 0Subtract 1 native both political parties of the equation:2x = -1 division both political parties of the equation by 2:x = -1/2 = -0.500

Solving 2x2-5x-3 = 0 directly Earlier us factored this polynomial by separating the center term. Permit us now solve the equation by perfect The Square and by making use of the Quadratic Formula

Parabola, finding the Vertex:4.1Find the vertex ofy = 2x2-5x-3Parabolas have actually a highest possible or a lowest allude called the Vertex.Our parabola opens up up and as necessary has a lowest point (AKA absolute minimum).We know this even before plotting "y" because the coefficient of the first term,2, is hopeful (greater 보다 zero).Each parabola has a vertical heat of symmetry the passes with its vertex. Because of this symmetry, the heat of the opposite would, because that example, pass with the midpoint the the two x-intercepts (roots or solutions) the the parabola. That is, if the parabola has actually indeed two real solutions.Parabolas deserve to model plenty of real life situations, such as the height over ground, of an object thrown upward, after some period of time. The peak of the parabola can provide us with information, such as the maximum height that object, thrown upwards, deserve to reach. Hence we desire to be able to find the works with of the vertex.For any parabola,Ax2+Bx+C,the x-coordinate of the vertex is provided by -B/(2A). In our situation the x coordinate is 1.2500Plugging right into the parabola formula 1.2500 for x we can calculate the y-coordinate:y = 2.0 * 1.25 * 1.25 - 5.0 * 1.25 - 3.0 or y = -6.125

Parabola, Graphing Vertex and also X-Intercepts :

Root plot for : y = 2x2-5x-3 Axis of the contrary (dashed) x= 1.25 Vertex in ~ x,y = 1.25,-6.12 x-Intercepts (Roots) : root 1 at x,y = -0.50, 0.00 source 2 at x,y = 3.00, 0.00

Solve Quadratic Equation by completing The Square

4.2Solving2x2-5x-3 = 0 by perfect The Square.Divide both sides of the equation by 2 to have 1 as the coefficient the the very first term :x2-(5/2)x-(3/2) = 0Add 3/2 come both side of the equation : x2-(5/2)x = 3/2Now the clever bit: take the coefficient of x, which is 5/2, division by two, providing 5/4, and finally square it giving 25/16Add 25/16 come both sides of the equation :On the ideal hand side us have:3/2+25/16The common denominator the the 2 fractions is 16Adding (24/16)+(25/16) gives 49/16So including to both sides we finally get:x2-(5/2)x+(25/16) = 49/16Adding 25/16 has actually completed the left hand side into a perfect square :x2-(5/2)x+(25/16)=(x-(5/4))•(x-(5/4))=(x-(5/4))2 things which are equal come the very same thing are also equal come one another. Sincex2-(5/2)x+(25/16) = 49/16 andx2-(5/2)x+(25/16) = (x-(5/4))2 then, according to the law of transitivity,(x-(5/4))2 = 49/16We"ll describe this Equation together Eq.

You are watching: Factor 2x^2-5x-3

See more: How Many Inches Is 12 Feet To Inches, Feet To Inches Converter

#4.2.1 The Square source Principle states that as soon as two things space equal, their square roots are equal.Note that the square source of(x-(5/4))2 is(x-(5/4))2/2=(x-(5/4))1=x-(5/4)Now, applying the Square root Principle to Eq.#4.2.1 we get:x-(5/4)= √ 49/16 add 5/4 come both sides to obtain:x = 5/4 + √ 49/16 since a square root has two values, one positive and the other negativex2 - (5/2)x - (3/2) = 0has 2 solutions:x = 5/4 + √ 49/16 orx = 5/4 - √ 49/16 keep in mind that √ 49/16 have the right to be created as√49 / √16which is 7 / 4